Lymphocyte Transformation in Syphilis: an In Vitro Correlate of Immune Suppression In Vivo? - Musher, Daniel M. (1975)
Suppression of cellular immunity during primary and secondary infection may explain, in part, the unusual clinical evolution of syphilis. We have previously shown that lymphocytes from normal subjects undergo blastic transformation when exposed in vitro to Treponema refringens. This response was suppressed in patients with syphilis. the suppression being unrelated to serum factors. In the present paper we studied lymphocyte response in vitro to T. refringens, T. reiter, and T. pallidum as well as to monilia and trychophytins. The response to these antigens was suppressed in patients with syphilis although the response to phytohemagglutinin. pokeweed mitogen, and streptolysin was normal. These data support the hypothesis that human infection with T. pallidum is followed by a complex interaction between cellular and humoral immunity, the former being suppressed in primary and secondary stages.